2021
DOI: 10.1186/s12951-021-01111-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of AD markers using naked eyes: point-of-care testing with paper-based lateral flow immunoassay

Abstract: Aβ42 is one of the most extensively studied blood and Cerebrospinal fluid (CSF) biomarkers for the diagnosis of symptomatic and prodromal Alzheimer’s disease (AD). Because of the heterogeneity and transient nature of Aβ42 oligomers (Aβ42Os), the development of technologies for dynamically detecting changes in the blood or CSF levels of Aβ42 monomers (Aβ42Ms) and Aβ42Os is essential for the accurate diagnosis of AD. The currently commonly used Aβ42 ELISA test kits usually mis-detected the elevated Aβ42Os, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…There was a good correlation (R 2 = 0.9796) between the T line signal intensity and the detection concentration within the concentration range of 0.18–1820 ng/mL ( Figure 7 c). Previous studies have reported that the Aβ42Os levels in the blood of AD patients range from 0.1 to 1 ng/mL, as detected by sandwich ELISA [ 31 ]. The sensitivity of the nanozyme-strip for Aβ42Os detection needs to be improved.…”
Section: Resultsmentioning
confidence: 99%
“…There was a good correlation (R 2 = 0.9796) between the T line signal intensity and the detection concentration within the concentration range of 0.18–1820 ng/mL ( Figure 7 c). Previous studies have reported that the Aβ42Os levels in the blood of AD patients range from 0.1 to 1 ng/mL, as detected by sandwich ELISA [ 31 ]. The sensitivity of the nanozyme-strip for Aβ42Os detection needs to be improved.…”
Section: Resultsmentioning
confidence: 99%
“…The first LFA, similar to those available today, was developed in the 1980s to detect the presence of human chorionic gonadotropin (hCG) in urine to confirm pregnancy . Since then, lateral flow tests have become successful analytical devices for PoC testing in various settings, ranging from detecting disease biomarkers, , pathogenic bacteria, viruses, and mycotoxins to chemical contaminants like veterinary drug residues or pesticides . Since the SARS-CoV-2 outbreak in 2019, LFAs have become one of the most abundant diagnostic tools for identification and monitoring of virus spread, needed to implement quarantine measures, despite their analytical drawbacks .…”
Section: Introductionmentioning
confidence: 99%
“…Especially immunoassays, when performed at the point of care (POC), could enable timely testing when a low turnaround time of analysis is highly needed, e.g., in first-aid settings (ambulance, physician offices, pharmacies). POC immunoassays also have great potential to assess time-critical and labile biomarkers, which are prone to degradation after sample collection. , Various lab-on-chip-type immunoassays, e.g., based on centrifugal or paper-based microfluidics, were proposed to realize POC applications. In these approaches, analyte capturing is typically achieved using immobilized antibodies, e.g., in porous matrices or on bead surfaces .…”
Section: Introductionmentioning
confidence: 99%